Several Norms and Beliefs, Defining the Attitude to Human Resources in the Industrial Organizations - Kiril Dimitrov (Economic Alternatives, 2009)
The current article reveals: the role of three norms from the environment, in which Bulgarian industrial enterprises operate; and the role of three beliefs, disseminated among the managers of these organizations. It is considered that their joint influence hampers the achievement of sustainable competitive advantage through human resources by the enterprises and may postpone the actual integration in the single European market after Bulgaria's accession to the European Union. Steps, mitigating the negative impact of these phenomena, are proposed.
Keywords: M12; M14; 330; human resource management; industrial enterprises; “employer – employee” relationship